Mass probation: Temporal and geographic correlation of county-level probation rates & mental health in North Carolina - Katherine LeMasters; Paul Delamater; Lauren Brinkley-Rubinstein; Jesse K. Edwards; Whitney R. Robinson; Brian Pence (Elsevier, 2023)
High community incarceration rates are associated with worse community mental health. However, it remains unknown whether higher rates of probation, a form of criminal legal community supervision, are similarly associated with worse community mental health. Our objective was to evaluate temporal and geographic correlations of county-level probation and mental health rates separately and to assess the association between county-level probation and mental health rates, measured by self-inflicted injury and suicide. We performed ecological analyses using North Carolina administrative data (2009-2019) and used repeated cross-section, multivariable spatial error models. From 2009 to 2019, probation rates trended downward while self-inflicted injury and suicide remained stable. We found positive spatial autocorrelation suggesting that there are spatial determinants of probation and self-harm, though less so for suicide. Hot spot analyses showed local variation with high self-harm and suicide rates being clustered in rural Western North Carolina and high probation rates being clustered in rural Eastern North Carolina. Probation was positively associated with self-inflicted injury and suicide. For example, in 2018, a 1 percentage point increase in probation was associated with a 0.05 percentage point increase in self-harm in 2019 (95% CI: 0.03, 0.06), meaning that in a county of 100,000 people, an increase in 1000 county residents being on probation would be associated with an increase in 50 self-harm injuries. High county-level probation rates may exert collateral damage on the mental health of those living in areas with much of the population under state control. These findings emphasize that the criminal legal system is not separate from communities and that future public health research and advocacy must consider these collateral consequences of probation on communities.